2015
DOI: 10.1063/1.4930534
|View full text |Cite
|
Sign up to set email alerts
|

Polarization contributions to intermolecular interactions revisited with fragment electric-field response functions

Abstract: The polarization energy in intermolecular interactions treated by self-consistent field electronic structure theory is often evaluated using a constraint that the atomic orbital (AO) to molecular orbital transformation is blocked by fragments. This approach is tied to AO basis sets, overestimates polarization energies in the overlapping regime, particularly in large AO basis sets, and lacks a useful complete basis set limit. These problems are addressed by the construction of polarization subspaces based on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
207
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 114 publications
(210 citation statements)
references
References 90 publications
2
207
1
Order By: Relevance
“…2.2, while in this work, the separation of POL and CT is achieved by using the original AO-block based ALMO scheme 110,123 instead of the recently proposed fragment electrical response function (FERF) model. 124 The FERF model gives a well-defined basis set limit to the resulting polarization energy but is computationally more expensive. This choice is made because smaller basis sets that are far from the complete basis set (CBS)…”
Section: Computational Detailsmentioning
confidence: 99%
“…2.2, while in this work, the separation of POL and CT is achieved by using the original AO-block based ALMO scheme 110,123 instead of the recently proposed fragment electrical response function (FERF) model. 124 The FERF model gives a well-defined basis set limit to the resulting polarization energy but is computationally more expensive. This choice is made because smaller basis sets that are far from the complete basis set (CBS)…”
Section: Computational Detailsmentioning
confidence: 99%
“…More details about the Hessian derivation (especially the R ∆∆ term) can be found in Ref. 133, which carefully derived the orbital rotation Hessian for SCF-MI. The preconditioner we apply to the L-BFGS algorithm is the inverted ondiagonal blocks of the Hessian, i.e., the inverse of H XX for all the different atom blocks (X).…”
Section: Acknowledgmentsmentioning
confidence: 99%
“…[161][162][163] In recently submitted work, we have used the second generation of (ALMO)-EDA [164][165][166] , combined with the high quality ωB97X-V density functional 128 , to compare against the energy decomposition of terms in the AMOEBA potential for the water dimer and various simple ionwater dimers 76 , an example of which is shown in Figure 6. For those interactions, we showed that the ωB97X-V/def2-QZVPPD level of theory is virtually equivalent to reference CCSD(T) calculations at the complete basis set limit, at a fraction of the computational cost, as CCSD(T) scales as O (N 7 ).…”
mentioning
confidence: 99%